(untitled) (Journal of Computational Mathematics, 2018)
In this paper we extend the idea of interpolated coefficients for a semilinear problem to the triangular finite volume element method. We first introduce triangular finite volume element method with interpolated coefficients for a boundary value problem of semilinear elliptic equation. We then derive convergence estimate in H^1-norm, L^2-norm and L^∞-norm, respectively. Finally an example is given to illustrate the effectiveness of the proposed method.